Screening Capsicum germplasm for resistance to tomato spotted wilt virus (TSWV) - Cebolla-Cornejo, Jaime; Soler, Salvador; Gomar, B.; Soria, D. M.; Nuez, Fernando (2017)
Resistance conferred by the Tsw locus from Capsicum chinense against Tomato spotted wilt virus (TSWV) has been widely used in breeding programmes. Nevertheless, this resistance depends on inoculation conditions, and isolates able to overcome it have already been detected. In this work 29 accessions of several Capsicum species have been mechanically inoculated with TSWV to identify new sources of resistance. Five accessions showed variable percentages of resistant plants, two of which did not show local lesions on inoculated leaves, suggesting that the response was not mediated through hypersensitivity. Two of these accessions also had a remarkable reduced viral accumulation compared to susceptible control. 'ECU-973', a C. chinense accession, showed the best performance against TSWV, with 100% resistant plants. This response was confirmed after mechanical inoculation with three different TSWV isolates. The resistance was maintained when the accession was inoculated with TSWV using a high pressure of viruliferous thrips. These results open new possibilities in the development of a durable resistance to TSWV in pepper.